Trabalho em equipe na reanimação cardiorrespiratória pediátrica: capacitação de estudantes de medicina com simulação realística - Beatriz Adriane Rodrigues Gonçalves (2021)
Introduction: teamwork is one of the major requirements in the highly complex system for providing care to pediatric critically ill patients. There is broad consensus in the literature of its direct link to quality and safety of care. Objectives: to summarize the evidence in the literature on the impact of teamwork training on the performance of professionals who provide care to pediatric critically ill patients; to evaluate the satisfaction of people who attended a training on pediatric cardiopulmonary resuscitation using high fidelity simulation; and to check if the specific approach on teamwork improves the technical and non-technical performance. Method: an integrative review was performed by searching for articles that studied the effect of teamwork on the care of pediatric critically ill patients in medical literature databases. Training was given to 65 Medical students on cardiac arrest care in children, according to the 2015 American Heart Association protocols. The intervention group also received training on teamwork with a customized version of the TeamSTEPPS® protocol. There was theoretical and practical evaluation before and after training, as well as a satisfaction questionnaire. Results: in the integrative review, the studies showed improvement in non-technical skills, self-efficacy, and/or safety culture when an intervention related to teamwork was performed; in addition to improvement in technical performance and clinical outcomes, when evaluated. Regarding the training carried out, in the theoretical test, there was no difference between the control and intervention groups, both pre-(p=0.291) and post-test (p=0.397), but in both there was an improvement in the score (p=0.000 and p=0.049). In the practice test checklist, both groups showed better percentages of right answers in the post-test (p=0.000); there was no difference between them in the pre-test (p=0.289), but, in the post-test, the intervention group achieved better scores (p=0.000). There was an increase in the number of team events in both groups in the post-test (p=0.000), with higher values in the intervention group in the pre-test (p=0.017) and in the post-test (p=0.009). Both groups presented improvement in the total time spent to perform the first resuscitation steps in the post-test (p=0.000), with reduction of 33.6% in the control group and 34.2% in the intervention group, but without difference between them in the pre-test (p=0.994) and in the post-test (p=0.819). Conclusions: evidence of the beneficial effect of teamwork on health care is growing, but, despite this, research in the pediatric area is still meager. Teamwork training using the customized TeamSTEPPS® protocol has improved teamwork and technical performance. The evaluation on the part of students regarding the received training was favorable.